Effectiveness of islamic value-based husband's assistance to reduce anxiety of third trimester pregnant women - Diana, Sirlii; Mufidah, Mufidah; Fatimah, Wahyu Dwi; Dewi, Nina Artika (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Anxiety levels in pregnant women during the third trimester often increase due to complex physical, hormonal, and psychological changes. If left untreated, this can negatively impact pregnancy and childbirth. Islam regulates the husband's role in various aspects, one of which is psychological and spiritual support. Purpose: To analyze the effectiveness of Islamic-based husband support in reducing anxiety in pregnant women during the third trimester. Method: This quasi-experimental study, with a pre-test-post-test design with a control group, was conducted from November 2024 to February 2025 at the Rejosari Community Health Center, Pringsewu Regency. The study population consisted of 60 pregnant women in their third trimester who met the inclusion and exclusion criteria, who were randomly divided into the intervention and control groups. The Perinatal Anxiety Screening Scale (PASS) was used to measure anxiety. Data were analyzed using the chi-square test for categorical data and the independent t-test for numerical data. Results: There were no differences in knowledge, husband support, and anxiety among pregnant women before the study between the two groups (p value >0.05; 95% CI). However, there were significant differences in knowledge, husband support, and a significant decrease in anxiety in the intervention group compared to the control group (p = 0.001; 95% CI). Conclusion: Husband support based on Islamic values ​​was statistically effective in increasing husbands' knowledge and support for pregnant women in the third trimester, resulting in a significant decrease in anxiety. Husband support based on Islamic values ​​needs to be integrated into antenatal care programs to strengthen family support for pregnant women. Suggestion: Further research with a larger sample size is recommended to develop a maternal health intervention model based on religious values. Keywords: Husband Support; Islamic Values; Pregnant Women's Anxiety. Pendahuluan: Tingkat kecemasan ibu hamil trimester III sering meningkat akibat perubahan fisik, hormonal, dan psikologis yang kompleks, jika tidak ditangani dapat berdampak negatif pada kehamilan dan persalinan. Islam mengatur peran suami dalam berbagai aspek, salah satunya adalah dukungan psikologis dan spiritual. Tujuan: Untuk menganalisis efektivitas pendampingan suami berbasis nilai-nilai islam dalam mengurangi kecemasan pada ibu hamil trimester III. Metode: Penelitian quasi eksperimen dengan desain pretest-posttest with control group, dilakukan pada November 2024 hingga Februari 2025, di Puskesmas Rejosari Kabupaten Pringsewu. Populasi penelitian ini adalah ibu hamil trimester III yang memenuhi kriteria inklusi dan eksklusi sebanyak 60 partisipan yang terbagi secara acak menjadi kelompok intervensi dan kontrol. Instrumen pengukuran kecemasan menggunakan Perinatal Anxiety Screening Scale (PASS). Data dianalisis menggunakan uji chi square untuk data kategori dan uji T independent test untuk data numerik. Hasil: Tidak terdapat perbedaan pengetahuan, dukungan suami, dan kecemasan ibu hamil sebelum penelitian pada kedua kelompok (p-value >0.05; CI 95%). Namun, terdapat perbedaan signifikan pengetahuan, dukungan suami, dan penurunan kecemasan yang signifikan pada kelompok intervensi, dibandingkan dengan kelompok kontrol (p = 0.001; CI 95%). Simpulan: Pendampingan suami berbasis nilai-nilai Islam terbukti efektif secara statistik dalam meningkatkan pengetahuan dan dukungan suami terhadap ibu hamil trimester III yang berdampak pada penurunan kecemasan secara signifikan. Pendampingan suami berbasis nilai-nilai Islam perlu diintegrasikan dalam program pelayanan antenatal untuk memperkuat dukungan keluarga terhadap ibu hamil. Saran: Penelitian lanjutan dengan cakupan sampel lebih luas disarankan untuk mengembangkan model intervensi berbasis nilai keagamaan dalam kesehatan maternal. Kata Kunci: Dukungan Suami; Nilai Islam; Kecemasan Ibu Hamil.